Conscientiousness, work-family-study conflict and general work stress amongst employed non-residential South African Military Academy students - Mashatola, Ngoako Japhta (Stellenbosch : Stellenbosch University, 2020)
Thesis (MCom)--Stellenbosch University, 2020.